A German machine for differencing and testing additives. Issue 3 (4th May 2017) - Alexander, John; Gallehawk, John; Jackson, John; Pearce, Allen; Simpson, Edward
ABSTRACT: The first-named author is a collector of "crypto" items. In this article, one recently acquired item is described, and speculation as to its use is made. The device could possibly be used to calculate differences with additive or subtractor ciphers, where a five-figure number must be either added to or subtracted from a code group. It has unusual, not to say mystifying, features. A description and photographs of this item are presented. Further information about this device would be welcomed.